The Influence of Organizational Culture and Motivation on the Performance of Secretarial Unit Employees at the West Java Provincial Education Service - Moh Aep Nurjamad; Asep Junardi (International Journal of Scientific Multidisciplinary Research, 2024)
The aim of this research is to find out how much influence organizational culture and motivation have on the performance of secretarial unit employees at the West Java Provincial Education Service. The research methods used are descriptive methods and associative methods. The population in this study was 129 employees. Based on the research results, it is known that descriptively the three variables, namely Organizational Culture, Motivation and Performance are in the Good category. And in associative research there is a partial and simultaneous positive influence on the variables Organizational Culture and Motivation on Performance. Partially, the influence of organizational culture on the performance of secretarial unit employees at the West Java Provincial Education Service is 43% and the influence of motivation on the performance of secretarial unit employees at the West Java Provincial Education Service is 40.1%. Simultaneously, the influence of organizational culture and motivation on the performance of secretarial unit employees at the West Java Provincial Education Service is 83.1%